Jordan : Seventh and Final Review Under the Stand-By Arrangement and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jordan's Seventh and Final Review Under the Stand-by Arrangement and Proposal for Post-program Monitoring. Jordan's program has helped the economy weather different shocks. Performance has been good in the run-up to the final review. Although growth has been affected by regional tensions, the current account deficit is narrowing, foreign reserves remain at an adequate level, and inflation is low. All end-April performance criteria were met with comfortable margins, and policies are on track to meet their 2015 targets while fiscal structural reform is moving forward. The IMF staff supports the completion of the seventh review and the related purchase.